2000
DOI: 10.1002/1096-8652(200007)64:3<175::aid-ajh6>3.3.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy alone versus surgery followed by chemotherapy for stage I/IIE large‐cell lymphoma of the stomach

Abstract: The optimal treatment of localized large-cell lymphoma of the stomach remains controversial. In particular, the role of surgical resection of the primary tumor needs to be clearly defined. We have reviewed all patients with a diagnosis of gastric lymphoma and treated in our institutions between 1988 and 1998. Patients fulfilling the following criteria were included in this study: (1) histologically proven large-cell lymphoma of the stomach; (2) adequate pathological materials and complete clinical information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…None of the patients experienced acute treatment related morbidity or mortality from local complications [68] . In three recent trials with variable chemotherapy regimens, the survival rates of 82%-88% in stage IE and IIE, high grade lymphoma with only few and manageable complications were found [65,67,68] . In other series, chemotherapy alone compared with surgical resection alone, has shown no significant difference in the matter of survival.…”
Section: Chemotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…None of the patients experienced acute treatment related morbidity or mortality from local complications [68] . In three recent trials with variable chemotherapy regimens, the survival rates of 82%-88% in stage IE and IIE, high grade lymphoma with only few and manageable complications were found [65,67,68] . In other series, chemotherapy alone compared with surgical resection alone, has shown no significant difference in the matter of survival.…”
Section: Chemotherapymentioning
confidence: 99%
“…In patients with comorbid factors and increased risk of surgery-related morbidity and mortality, chemotherapy offered an effective or equally effective mode of treatment to surgical resection 57% vs 58% [71] . The fear of chemotherapy-related complications, for instance, bleeding and perforation, has been disputed, and less significant compared with surgical resection [65,[67][68][69] . Some authors reported the incidence of chemotherapy-related bleeding between zero and three percent and no perforation [60,72] .…”
Section: Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been our policy to administer systemic chemotherapy comprised of anthracycline‐ or anthracenedione‐containing regimens as the initial therapy for all patients who have primary high grade gastric lymphoma 15. Surgery and local radiation are reserved for patients whose disease does not respond well to chemotherapy or who develop treatment‐related complications that prohibit further treatment.…”
Section: Methodsmentioning
confidence: 99%
“…There is considerable controversy concerning gastric lymphoma treatment since there are several therapeutic options. Surgical resection, the classical treatment associated with good results, is increasingly being replaced by chemotherapy (2,3), also showing good results but lacking long-term follow-up. Its pathogenesis has been associated with Helicobacter pylori (H. pylori) infection and thus these patients have also been exclusively treated with H. pylori eradication therapy, with complete remission in high percentages (62-91,6%) (4,5).…”
Section: Introductionmentioning
confidence: 99%